2009
DOI: 10.1161/strokeaha.109.549691
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Are Early Responders After Hypoxia-Ischemia in Immature Rat Brain

Abstract: Background and Purpose-Perinatal hypoxia-ischemia (HI) produces acute and prolonged inflammation of the brain.Mast cells (MCs), numerous in the pia and CNS of neonatal rats, can initiate inflammation attributable to preformed mediators. MCs contribute to HI brain damage in the neonatal rat; MC stabilization protects through 48 hours of reperfusion. Here we hypothesize that HI induces early MC migration, activation, and release of proinflammatory molecules. Methods-HI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 38 publications
5
106
2
Order By: Relevance
“…A previous study suggested that activated MCs but not microglia were the "first responders" in brain injury [38]. Although other resident cells in the CNS produce TNF-α (most notably microglia [39,40] and endothelial cells [41]), the presence and release of TNF-α from MCs precedes its detection in other cells.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study suggested that activated MCs but not microglia were the "first responders" in brain injury [38]. Although other resident cells in the CNS produce TNF-α (most notably microglia [39,40] and endothelial cells [41]), the presence and release of TNF-α from MCs precedes its detection in other cells.…”
Section: Discussionmentioning
confidence: 97%
“…8,11 The molecular mechanisms behind such action, however, have remained elusive. Here, we provide mechanistic insight into the processes leading to BBB disruption following reperfusion-induced MC activation.…”
Section: Discussionmentioning
confidence: 99%
“…The latter are normally resident in the CNS [62], in close association with cerebral blood vessels during development and adulthood [63,64]. In contrast with what had been long assumed [65], Jin et al [66] showed that mast cell activation is the 'first responder' in this injurynot microglia. Although TNF-a is produced by many cells in response to stimuli, mast cells arrive 'armed' to initiate acute inflammation with their store of preformed TNF-a [67].…”
Section: Microglia Mast Cells and Nervous System Pathology (A) Neuromentioning
confidence: 99%